2020
DOI: 10.1186/s12884-020-2744-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of sFlt1/PlGF ratio as a marker for preeclampsia

Abstract: Background: Preeclampsia (PE) is a serious complication of pregnancy and one of the main causes of maternal and neonatal mortality and morbidity in the world. Finding a biomarker with high sensitivity and specificity could lead to prediction and early diagnosis of the disease and reduces its complications. In this study, we evaluated diagnostic accuracy of Soluble fms-like tyrosine kinase-1 (sFlt-1) to Placental growth factor (PlGF) ratio for diagnosis of PE. Methods: The cases included 23 mild, 15 severe pree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 25 publications
2
29
0
1
Order By: Relevance
“…The sFlt-1/PIGF ratio was not significantly increased in severe PE than mild PE (p = 0.0795) as documented in other studies. Our finding was however, similar to that documented by Nikuei et al, who observed that although the ratio was higher in severe PE than mild PE, the difference was not statistically significant, p = 0.389 [20]. Chaiworapongsa and co-workers [14] documented that increasing sFlt-1 correlates with disease severity, this was not observed in this study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The sFlt-1/PIGF ratio was not significantly increased in severe PE than mild PE (p = 0.0795) as documented in other studies. Our finding was however, similar to that documented by Nikuei et al, who observed that although the ratio was higher in severe PE than mild PE, the difference was not statistically significant, p = 0.389 [20]. Chaiworapongsa and co-workers [14] documented that increasing sFlt-1 correlates with disease severity, this was not observed in this study.…”
Section: Discussionsupporting
confidence: 88%
“…One of such markers is the alterations in maternal serum concentrations of anti-angiogenic (sFlt-1) and pro-angiogenic factors (VEGF and PlGF) [11]. Interestingly, the sFlt-1/PlGF ratio has been demonstrated to show better performance than single markers in predicting the risk of PE [19] [20]. The alteration of the balance between concentration of pro-angiogenic factors, VEGF and PIGF, and anti-angiogenic factors like sFlt-1 and Endoglin has been documented in the pathophysiology of preeclampsia [21].…”
Section: Introductionmentioning
confidence: 99%
“…PE progresses rapidly. There are currently no specific laboratory indicators to diagnose and grade the severity of PE patients, which may have an impact on the subsequent treatment of patients (8,9). The anti-angiogenic factor sFlt-1 is secreted by the placenta and is involved in vascular regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The ROC curve results in this study show that sFlt-1, CXCL16, and LCN-2 all have good sensitivity for the diagnosis of PE, among which LCN-2 is the best for the diagnosis of PE, as it reached a diagnostic sensitivity of 93.33% and an AUC of 0.831. Insufficient blood supply to the placenta leads to the increase in sFlt-1 content, and the increase in sFlt-1 leads to angiogenesis dysfunction, damaged endothelial cells, and subsequent inflammation and PE (9). Inflammation and endothelial damage can induce high expression of LCN-2, which can possibly cause vascular sclerosis to aggravate PE (14).…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the VEGF family, PLGF is considered as a biomarker in PE and its development. 19,49,50 Uteroplacental ischemia in PE can significantly reduce the PLGF expression in nonhuman primate, and PLGF treatment can reduce blood pressure and proteinuria. 51,52 However, a report demonstrated that PLGF is not statistically significant compared with the control group at the mRNA level.…”
Section: Discussionmentioning
confidence: 99%